Degradation of formaldehyde from plywood with an iron electrode in alkaline solution. (15th June 2019) - Zhou, Bin; Lin, Xin-Zhi; Zhang, Yu-Gui; Shiue, Angus; Hu, Shih-Cheng; Liu, Hui-Fang; Wang, Yu; Qiu, Shou-Meng; Dong, Zhi-Bo; Lu, Song
Abstract: Formaldehyde emitted from formaldehyde-based adhesive profoundly affects human health. Accordingly, increasing attention has been paid to developing effective source-control measures to reduce the amount of formaldehyde released from plywood. In this study, the formaldehyde removal performance of a combined ammonia and electric field plywood treatment method was investigated. By performing orthogonal experiments, the respective influences of the concentration of ammonium hydroxide solution, intensity of the electric field, heating temperature, and heating time were analyzed. It was found that the concentration of formaldehyde released from the plywood was reduced by 48% using the ammonia and electric-field method. In addition, the treatment method was applied to high-emitting plywood. Here, it was found that a higher formaldehyde concentration within the untreated samples corresponded to a higher removal rate. The intensity of the electric field was the most influential factor affecting the performance of the method. The optimal operating conditions for the orthogonal experiment corresponded to a 12.5% concentration of ammonium hydroxide solution, an electric field intensity of 25 V, a heating temperature of 343 K and a heating time of 150 min. The ammonia and electric field treatment method can effectively reduce the concentration of formaldehyde emitted from plywood. Therefore, it can be applied as a promising method for pollution source control.